Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pbio.3000221
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 signalling dynamics promote neural differentiation by regulating chromatin accessibility and the polycomb repressive complex

Abstract: Fibroblast growth factor (FGF) is a neural inducer in many vertebrate embryos, but how it regulates chromatin organization to coordinate the activation of neural genes is unclear. Moreover, for differentiation to progress, FGF signalling must decline. Why these signalling dynamics are required has not been determined. Here, we show that dephosphorylation of the FGF effector kinase ERK1/2 rapidly increases chromatin accessibility at neural genes in mouse embryos, and, using ATAC-seq in human embryonic stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 137 publications
0
24
0
1
Order By: Relevance
“…In this sense, it has been proposed that GSK3‐β deletion removes homeostatic controls on neural progenitors, shifting the balance toward self‐renewal, massively expanding the radial progenitor pool, and leading away from neurogenesis (Kim et al, 2009). Unexpectedly, we found that the ERK1/2 pathway was decreased in brains with high levels of SVCT2 although it has been shown that overexpression of SVCT2 and treatment with AA promoted ERK1/2 phosphorylation, stimulating neuronal differentiation (Li et al, 2006; Salazar et al, 2016; Semprich et al, 2022). However, it has also been demonstrated that ERK1/2 inhibits neuronal differentiation of neural stem cells (Wang et al, 2009) and upregulates the expression of astrocyte‐related genes (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this sense, it has been proposed that GSK3‐β deletion removes homeostatic controls on neural progenitors, shifting the balance toward self‐renewal, massively expanding the radial progenitor pool, and leading away from neurogenesis (Kim et al, 2009). Unexpectedly, we found that the ERK1/2 pathway was decreased in brains with high levels of SVCT2 although it has been shown that overexpression of SVCT2 and treatment with AA promoted ERK1/2 phosphorylation, stimulating neuronal differentiation (Li et al, 2006; Salazar et al, 2016; Semprich et al, 2022). However, it has also been demonstrated that ERK1/2 inhibits neuronal differentiation of neural stem cells (Wang et al, 2009) and upregulates the expression of astrocyte‐related genes (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 59%
“…Unexpectedly, we found that the ERK1/2 pathway was decreased in brains with high levels of SVCT2 although it has been shown that overexpression of SVCT2 and treatment with AA promoted ERK1/2 phosphorylation, stimulating neuronal differentiation (Li et al, 2006;Salazar et al, 2016;Semprich et al, 2022). However, it has also been demonstrated that ERK1/2 inhibits neuronal differentiation of neural stem cells (Wang et al, 2009) and upregulates the expression of astrocyte-related genes (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 66%
“…One intriguing possibility, supported by previous ChIP-Seq results, is that Cic leaves hkb’s enhancers more slowly than those of tll ( Figure S6 ) (Keenan et al 2020). It is also possible that signaling dependent chromatin changes are involved (Semprich et al 2022; Hannon et al 2017). These models will be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we asked how Hes1 dynamics changed upon induced differentiation. Since FGF inhibition induces differentiation of pre-NT to NT 25,27,52 and PSM to somite 53,54 , we inhibited FGF activity in 2D spread-out cultures using SU5402 (Fig. 6).…”
Section: Induced Differentiation To Neural Tube By Fgf Inhibition Res...mentioning
confidence: 99%
“…NMPs transitioning from the TB to the NT pass through the preneural tube (pre-NT), surrounded by oscillating PSM 25 . FGF signalling prevents premature differentiation in the pre-NT, while Notch signalling supports cell proliferation 26,27 . In the anterior NT, neural progenitor cells continue to proliferate and differentiate into future spinal cord neurons.…”
Section: Introductionmentioning
confidence: 99%